Performance Comparison of Public Hospitals Between 2014 and 2018 in Different Regions of Guangdong Province, China, Following 2017 Medical Service Price Reforms - Weng, Kai-Yuan; Xia, Feng; Lin, Wen-Qi; Wang, Yi-Bao (Frontiers in Public Health, 2021)
This study analyzed performance of public hospitals and regional differences in performance following reform of medical service prices in Guangdong province, China. From three cities in four regions, we randomly selected a total of 12 traditional Chinese medicine hospitals and 12 general tertiary hospitals. Six questionnaires were completed by the hospitals, using 2014–2018 internal data. Principal components analysis was used to compare performances of the hospitals and regions following price reform. The extent to which medical service prices were adjusted varied considerable for different procedures in the same region and for the same category of procedures among regions. After reform, compensation for medical services in public hospitals reached the target of 80%, except in the Western region. However, annual growth of costs to patients was generally above 4%; the burden on patients was not alleviated by fee control. Reforms were more effective for comprehensive than Chinese traditional medicine hospitals. Performance scores of general hospitals in the Pearl River Delta, Eastern, Western, and Northern regions were 1.24, 1.16, −0.22, and −1.01, respectively. This is consistent with ranking by level of economic development of each region. The government should implement a regional medical service pricing mechanism. Additionally, comprehensive and traditional Chinese medicine hospitals should each have appropriate pricing policies. Future policies should focus on controlling costs incurred by patients.